(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2014)
This study is conducted to produce two-tier diagnostic instruments which are able to detect misconceptions in stoichiometry, hydrocarbon and reaction rate topics. Descriptive method was used in developing two-tier instruments for stoichiometry and reaction rate topics, while for hydrocarbon topic the method that used was Research and Development (R&D) method. The two-tier instruments are developed through essay test, interview to students and multiple choices problems. Validity test of these instruments shows that the numbers of questions that are judged as valid are 15 questions for stoichiometry topic, 18 questions for hydrocarbon topic and 21 questions for reaction rate topic. These instruments were tested to 10th and 11th grade of senior high school students. The results of the tests are analyzed and interpreted so the misconceptions can be identified. The findings of this research show that identified students‟ misconceptions of stoichiometry through two-tier instrument are including basic law of chemistry and mol concept. The misconceptions of hydrocarbon topic are including characteristics of carbon, bonding in carbon chain and closed carbon chain structure. Meanwhile, the misconceptions of reaction rate topic are including definition of reaction rate, reaction rate order, collision theory and factors affecting reaction rate. Penelitian ini dikembangkan untuk menghasilkan instrumen diagnostik two tier yang dapat mendeteksi miskonsepsi siswa pada materi stoikiometri, hidrokarbon, dan laju reaksi. Metode deskriptif digunakan untuk mengembangkan instrumen pada materi stoikiometri dan laju reaksi sedangkan metode R&D digunakan untuk mengembangkan instrumen pada materi hidrokarbon. Kualitas instrumen diagnostik two-tier diuji dengan validitas dan reliabilitas. Uji validitas instrumen menunjukkan bahwa jumlah butir soal yang dinilai valid, yaitu 15 butir soal pada materi stoikiometri, 18 dari 39 butir soal pada materi hidrokarbon, dan 21 dari 56 butir soal pada materi laju reaksi. Instrumen tersebut kemudian diujikan kepada siswa SMA kelas X dan XI. Hasil tes tersebut dianalisis dan diinterpretasikan, sehingga miskonsepsi dapat teridentifikasi. Temuan dari penelitian ini menunjukkan bahwa miskonsepsi siswa pada materi stoikiometri meliputi hukum-hukum dasar kimia dan konsep mol. Miskonsepsi siswa pada materi hidrokarbon meliputi kekhasan atom karbon, ikatan atom dalam rantai karbon, dan rantai tertutup. Sementara itu, miskonsepsi siswa pada materi laju reaksi meliputi pengertian laju reaksi dan faktor-faktor yang mempengaruhi laju reaksi.